Increased myocardial stiffness more than impaired relaxation function limits cardiac performance during exercise in heart failure with preserved ejection fraction: a virtual patient study. Issue 1 (23rd November 2020) - van Loon, Tim; Knackstedt, Christian; Cornelussen, Richard; Reesink, Koen D; Brunner La Rocca, Hans-Peter; Delhaas, Tammo; van Empel, Vanessa; Lumens, Joost
Abstract: Aims: The relative impact of left ventricular (LV) diastolic dysfunction (LVDD) and impaired left atrial (LA) function on cardiovascular haemodynamics in heart failure with preserved ejection fraction (HFpEF) is largely unknown. We performed virtual patient simulations to elucidate the relative effects of these factors on haemodynamics at rest and during exercise. Methods and results: The CircAdapt cardiovascular system model was used to simulate cardiac haemodynamics in wide ranges of impaired LV relaxation function, increased LV passive stiffness, and impaired LA function. Simulations showed that LV ejection fraction (LVEF) was preserved (>50%), despite these changes in LV and LA function. Impairment of LV relaxation function decreased E / A ratio and mildly increased LV filling pressure at rest. Increased LV passive stiffness resulted in increased E / A ratio, LA dilation and markedly elevated LV filling pressure. Impairment of LA function increased E / A ratio and LV filling pressure, explaining inconsistent grading of LVDD using echocardiographic indices. Exercise simulations showed that increased LV passive stiffness exerts a stronger exercise-limiting effect than impaired LV relaxation function does, especially with impaired LA function. Conclusion: The CircAdapt model enabled realistic simulation of virtual HFpEF patients, covering a wide spectrum of LVDD and related limitations of cardiac exercise performance, all with preserved resting LVEF. Simulations suggest that increased LV passive stiffness, more than impaired relaxation function, reduces exercise tolerance, especially when LA function is impaired. In future studies, the CircAdapt model can serve as a valuable platform for patient-specific simulations to identify the disease substrate(s) underlying the individual HFpEF patient's cardiovascular phenotype. Graphical Abstract: